Gambaran Pemilihan Bahan dan Higienitas Pengolahan Makanan Balita di Posyandu Wonotingal Kecamatan Candisari Semarang - Devi, Chindya Paramitha; Untari (Jurnal Informatika dan Kesehatan, 2025)
Nutritional problems in Indonesia occur due to various factors, such as food intake, environment including hygiene and sanitation, socio-economic, family characteristics, and the presence of infection. Children who have poor nutritional status are susceptible to infection, because children were lack of immunity. Conversely, children who suffer from infections do not have sufficient appetite, resulting in children being malnourished and falling into poor nutritional status. So, infection and nutritional status were correlated. Malnutrition in children is influenced by the level of knowledge, attitudes and behavior of mothers in choosing the right food ingredients. The practice of selecting ingredients and hygiene of food processing is closely related to the emergence of certain diseases or infections, so further research is needed. This descriptive study focused on the description of the selection of ingredients and processing of toddler food by mothers, which wass carried out using a research instrument in the form of a questionnaire. The results of the study of 20 respondents (mothers of toddlers) conducted at the Posyandu of Wonotingal Village regarding the practice of mothers in preparing food for children (toddlers) were classified as "Defficient" in terms of the aspect of selecting ingredients and hygiene aspects of food processing, namely with indicators of selecting types of spices and toddler snacks, as well as the implementation of Clean and Healthy Living Behavior.   ABSTRAK Masalah gizi di Indonesia terjadi karena beragam faktor, seperti asupan makanan, lingkungan termasuk higiene dan sanitasi, sosial ekonomi, karakteristik keluarga, adanya infeksi. Anak yang mempunyai status gizi kurang mudah terkena infeksi, karena anak tidak mempunyai daya tahan tubuh yang cukup. Sebaliknya, anak yang menderita infeksi tidak mempunyai nafsu makan yang cukup, akibatnya anak kekurangan gizi dan jatuh pada status gizi kurang, sehingga keterkaitan infeksi dengan status gizi mempunyai hubungan timbal balik yang kuat. Kurangnya gizi pada anak dipengaruhi oleh tingkat pengetahuan, sikap dan perilaku ibu dalam memilih bahan makanan yang benar. Praktik pemilihan bahan dan higienitas pengolahan bahan pangan erat kaitannya dengan munculnya penyakit atau infeksi tertentu, sehingga dibutuhkan penelitian lebih lanjut. Penelitian deskriptif ini berfokus pada gambaran pemilihan bahan dan pengolahan bahan makanan balita oleh Ibu, yang dilakukan dengan instrumen penelitian berupa kuisioner. Hasil penelitian terhadap sejumlah 20 responden (ibu balita) yang dilaksanakan di Posyandu Kelurahan Wonotingal terkait praktik ibu dalam penyiapan makanan anak (balita) tergolong “Kurang Baik” ditinjau dari aspek pemilihan bahan dan aspek higienitas pengolahan pangan, yaitu dengan indikator pemilihan jenis bumbu dan makanan selingan balita, serta penerapan Perilaku Hidup Bersih dan Sehat (PHBS).